Whiteface versus Black Performance: Accounts of Black and Afro-descendant Performers in Portuguese America - Mayor, Mariana [UNESP] (Johns Hopkins University Press, 2022)
This study of theatrical performance in Portuguese America examines the prevalence of Black and African descendant performers onstage, whether enslaved or free. On the one hand, I consider the artistic implications of these performers' prominence in terms of how their performances fused European theatrical elements, for instance, with plays being staged in opera houses and featuring works by Pietro Metastasio and Carlo Goldoni. Other engagements with the European tradition suggest Spanish influences, such as performances of comedias and comic farces (entremezes). On the other hand, we find Afro-diasporic performance practices on the Portuguese American stage. Additionally, I address methodological challenges: How can this kind of theatricality be analyzed? Is it possible to reconstitute such scenes of Black performance and analyze acting methods, notwithstanding the scarce documentation? Finally, must we interrogate the connections between social organization in colonial Brazil's slave-holding society and forms of artistic expression. Sources mobilized for these queries include travelers' descriptions of performances, documents found in archival sources, and firsthand accounts of fêtes.